Luteolin improves nephropathy in hyperglycemic rats through anti-oxidant, anti-inflammatory, and anti-apoptotic mechanisms. (March 2023) - Chen, Li-You; Cheng, Hsin-Lin; Liao, Chih-Kai; Kuan, Yu-Hsiang; Liang, Tang-Jun; Tseng, To-Jung; Lin, Hsing-Chun
Graphical abstract: Highlights: Luteolin prevents the progression of STZ-induced abnormal serum biochemical parameters. Luteolin prevents the progression of STZ-induced abnormal serum biochemical parameters. Luteolin inhibits NF-κB-mediated pro-inflammatory cytokines and caspase 3-involved apoptosis. Luteolin enhances Nrf2-dependent antioxidant capacity. Abstract: Hyperglycemia can also induce the production of free radicals and the progression of inflammatory reactions. The aim of this study is to explore the potential anti-oxidant and anti-inflammatory mechanisms of luteolin in the treatment of diabetic nephropathy. Luteolin significantly reduced blood glucose and BUN levels in streptozotocin-induced diabetic rats and increased serum sodium and chloride levels. Histopathological staining of the kidney showed that luteolin effectively inhibits glycoprotein deposition and production of collagen fibers in the kidney. On Western blotting, luteolin increased anti-oxidant enzymes in the kidney by up-regulating NF-E2-related factor 2 (Nrf2). In DML rats, the expression of inflammatory cytokines decreased significantly with down-regulation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB). In addition, luteolin inhibited the activation of phosphoinositide 3-kinase/protein kinase B (PI3K/Akt) signaling pathway and the expressions of its downstream apoptosis-related proteins. In conclusion, luteolin slows the progression of nephropathy through anti-hyperglycemic, anti-inflammatory, anti-oxidant, and anti-apoptotic mechanisms.